The Effect of the STEAM Learning Model on Problem-Solving Skills in Science Education for Third-Grade Students at SDN Kamasan 1 - Paridah, Nur; Sopandi, Wahyu; Nurulpaik, Iik; Fitriani, Yulianti; Rokayah, Eroh (International Conference on Elementary Education, 2025)
Science and Social Studies (IPAS) learning in elementary schools plays a crucial role in developing students’ critical and problem-solving abilities. However, preliminary observations at SDN Kamasan 1, Cinangka District, revealed that third-grade students still struggle to identify problems and design contextual solutions in IPAS learning activities. This study aims to determine the effect of the STEAM (Science, Technology, Engineering, Art, and Mathematics) learning model on students’ problem solving skills. The research employed a quasi-experimental design with a non-equivalent control group, involving 52 students divided into an experimental class (n = 26) and a control class (n = 26). The experimental class received learning through the STEAM model, while the control class used conventional learning. Data were collected through problem-solving tests and observation sheets, and analyzed using an independent sample t-test. The results showed that the mean posttest score of the experimental class (M = 84.12, SD = 6.45) was significantly higher than that of the control class (M = 72.31, SD = 7.28), with t(50) = 6.42, p < 0.001. The effect size (Cohen’s d = 1.15) indicated a strong influence of the STEAM model on students’ problem-solving skills. These findings suggest that the STEAM learning model effectively enhances students’ ability to connect IPAS concepts to real-life situations, promoting creativity and collaboration in 21st-century learning contexts.